Clinical And Operational Advantages Of The LUCAS Mechanical Chest Compression Device In Emergency Medical Services: A Comprehensive Review Of Resuscitation Quality, Survival Outcomes, And System Efficiency (The Review of Diabetic Studies, 2025)
Out-of-hospital cardiac arrest presents a persistent clinical and operational challenge for prehospital Emergency Medical Services Systems, where interruptions, rescuer fatigue, and unsafe manual CPR during transport compromise resuscitation reliability. The LUCAS Mechanical Chest Compression Device has emerged as a key human–machine solution to standardize chest compression delivery in dynamic prehospital environments. This comprehensive review synthesizes global evidence from 2016 onward examining its effect on resuscitation quality, survival outcomes, provider safety, and system-level efficiency. Findings consistently demonstrate that the device delivers stable guideline-aligned depth and rate, increases compression fraction, and minimizes no-flow intervals, while supporting improved physiological perfusion markers and favorable trends in return of spontaneous circulation and neurological recovery after cardiac arrest. Operationally, the device improves crew task allocation, reduces the need to stop ambulances to maintain CPR, and enables clinicians to remain restrained and seated safely while compressions continue, expanding procedural capacity for airway management, vascular access, ECG analysis, drug preparation, and timely clinical documentation. Despite training, cost, and power-dependency challenges, LUCAS integration strengthens CPR precision and mission reliability while elevating paramedic safety and system performance indicators. Evidence supports broader adoption within structured EMS SOPs, clinical governance frameworks, and future AI-augmented CPR analytics to optimize human-device resuscitation synergy.